Kompetensi Guru dalam Menghadapi Tantangan Pendidikan di Era Digital - Triana Wulandari; Nurhidayah; Hasnatul Mardia; Yunita Sari (JPT : Jurnal Pendidikan Tematik, 2025)
Abstrack Teachers' competence in facing educational challenges in the digital era has become a crucial issue along with the rapid development of information and communication technology. The digital era brings significant changes in teaching and learning, which requires teachers not only to have good pedagogical skills but also the ability to integrate technology in the learning process. This article aims to explore the various competencies needed by teachers, including an understanding of educational technology, the ability to use digital media effectively, and the skills to adapt teaching methods to the needs and characteristics of increasingly diverse learners. It also identifies the challenges teachers face in adopting technology, such as limited access to resources, lack of adequate training and shifting patterns of interaction between teachers and students. For this reason, continuous professional development efforts are needed so that teachers can optimize their role in creating innovative and relevant learning in the digital era. By strengthening teachers' digital competencies, it is hoped that education can be more adaptive and ready to face the demands of the times.